The Development of Anchor-Based Podcasts to Improve Pronunciation Skills of Grade XI Students at SMA Negeri 3 Kutacane in English Learning - M.S, Marhamah (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to develop an Anchor-based podcast as an innovative learning medium to enhance the pronunciation skills of high school students in English. The research method employed is Research and Development (R&D), referring to the Borg & Gall (1983) model, which has been modified into seven stages: needs analysis, planning, product development, expert validation, limited trials, product revision, and large-scale trials. The study subjects consisted of 12 students for limited trials and 31 students for large-scale trials at SMA Negeri 3 Kutacane. Data were collected through observations, questionnaires, pronunciation tests (pretest-posttest), and expert validation. The results indicate that the Anchor-based podcast effectively improves students' pronunciation skills, with an average score increase from 62.5 (pretest) to 78.9 (posttest) in the limited trial and from 61.7 (pretest) to 80.4 (posttest) in the large-scale trial. Statistical analysis using a paired sample t-test (α = 0.05) confirmed this improvement as significant, with Cohen’s d effect sizes of 1.2 (limited trial) and 1.4 (large-scale trial), categorized as a large effect. Students and teachers responded positively to the podcast, with 75% of students finding it helpful and 90% of teachers agreeing on its effectiveness as a learning medium. However, some limitations, such as dependence on internet connectivity and overly long episode durations, need to be addressed. This study concludes that the Anchor-based podcast is a viable, cost-effective, and accessible pronunciation learning medium, contributing to the development of innovative English learning methods in the digital era.